Financial rick management : - Allen, Steven (Wiley, 2013)
In the Second Edition of Financial Risk Management + Website, market risk expert Steve Allen offers an insider's view of this discipline and covers the strategies, principles, and measurement techniques necessary to manage and measure financial risk. Fully revised to reflect today's dynamic environment and the lessons to be learned from the 2008 global financial crisis, this reliable resource provides a comprehensive overview of the entire field of risk management.